AUV Online Path Planning Strategy Based on Sectorial Gridded Detection Area - Yang Liu; Jinxi Sun; Guojie Li; Xiujun Xu (Journal of Marine Science and Engineering)
In this study, an online path planning strategy capable of traversing narrow passages is proposed for an autonomous underwater vehicle equipped only with forward-looking sonar in unknown environments. First, to establish the environment model, the sonar fan-shaped detection area is subdivided into multiple sectorial grids. Then, a comprehensive cost function combining safety, smoothness, and cost is utilized to generate the optimal heading. Furthermore, to safely pass through narrow passages, a sequence of subgoals for polynomial trajectory planning are determined on the perpendicular bisector ahead of the central line. The simulation results demonstrate the effectiveness of the proposed strategy, which determines the optimal heading through fan-shaped grid costs and generates a safe and smooth path. The AUV can achieve more safety navigating in obstructed areas and narrow passages.